(untitled) (Development Service Industry Management, 2025)
The purpose of this study is to analyze the role of trade unions in modern labor relations, focusing on their economic and social impact in both developed and developing countries. The study investigates key trends in union membership across countries, challenges posed by globalization, and the adaptation strategies of trade unions. This research employs a comparative analysis of statistical data on union membership trends and a review of recent academic literature on union efficacy and worker representation. Data from international organizations such as the ILO and OECD support the cross-country comparison, with emphasis on labor policies, socio-economic contexts, and changes in employment structures. Empirical data on union density and qualitative findings are used to illustrate key dynamics. The analysis reveals a general decline in union membership in developed countries, contrasted with varying trends in emerging economies. The findings suggest that union effectiveness is influenced by regional socio-economic factors and that unions in high-density countries, such as the Nordics, retain influence due to historical integration into labor policies. However, unions globally face challenges from informal and gig economies, which have prompted digital adaptation strategies in some regions. The results are useful for policymakers and labor organizations seeking to understand union dynamics in contemporary labor markets. Recommendations include supporting union adaptation to digital workspaces and advocating policies that extend union protection to non-standard forms of employment. This study provides a comprehensive overview of trade union challenges and adaptation methods in various economic contexts, highlighting the differences between high- and low-union-density countries. By addressing digitalization and gig economy trends, this paper offers insights into future strategies for sustaining union relevance in a changing labor landscape.